ANTIOXIDANT ACTIVITY OF SELECTED FORMULA Spirulina platensis TROCHES BASED ON PYSICAL CHARACTERISTICS - Ria Fahleny; Wini Trilaksani; Iriani Setyaningsih (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
ABSTRACT Spirulina contains complete nutrition and bioactive components as a source of antioxidants. The aims of this research were to determine a formula of troche from Spirulina platensis according to the physical characteristic standard of the Indonesian Health Ministry, and to determine the antioxidant activity of the selected troche from Spirulina platensis. This research was conducted in three stages. The first stage was troches formulation. The second stage was troches physical analyses, including weight uniformity, friability, hardnes, and disintegration time. The third stage was to determine the antioxidant activity of the selected formula of troche from Spirulina platensis. There were five formulas of troches i.e., FTS 1, FTS 2, FTS 3, FTS 4, and FTS 5. The troche consisted of Spirulina platensis powder, carrageenan, gelatin, corn flour, sugarleaf, and mint powder. Based on the weight uniformity of the troche, all formulas met the standard. However, according to friability aspect, the best formula was FTS 1 with rate of 1.7%. The hardness of five formula ranged from 0.65 to 2.3 Kp, and none met the standard. The best formula based on disintegration time measurement was FTS 1 (24:47 minutes). Based on the physical characteristics of the troches, the selected formula was FTS 1. The antioxidant activity (IC50 of the selected formula (FTS 1) was 288,68 ppm.   Keywords: antioxidant, troches, physical characteristics of troches, Spirulina platensis